CGIAR genebank viability data reveal inconsistencies in seed collection management - Hay, Fiona R.; Whitehouse, Katherine J.; Ellis, Richard H.; Sackville-Hamilton, N. Ruaraidh; Lusty, Charlotte E.; Ndjiondjop, Marie Noelle; Tia, Daniel; Wenzl, Peter; Santos, Luís Guillermo; Yazbek, Mariana; Azevedo, Vania C.R.; Peerzada, Ovais H.; et al. (Elsevier, 2021)
Genebanks underpin global food security, conserving and distributing agrobiodiversity for use in research and breeding. The CGIAR collections include >700,000 seed accessions, held in trust as global public goods. However, the role of genebanks in contributing to global food security can only be realized if collections are effectively managed. Examination of the historical viability monitoring data from seven CGIAR genebanks confirmed that high seed viability was maintained for many decades for the various crops and forage species. However, departures from optimum management procedures were revealed, and there were insufficient data gathered to derive reliable estimates of longevity needed to better forecast regeneration requirements, estimate the size of seed lots that should be stored, and optimize accession monitoring intervals.